2017
DOI: 10.1002/hbm.23694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different analysis approaches for DTI free-water corrected and uncorrected maps in the study of white matter microstructural integrity in individuals with depression

Abstract: Diffusion tensor imaging (DTI) has often been used to examine white matter (WM) tract abnormalities in depressed subjects, but these studies have yielded inconsistent results, probably, due to gender composition or small sample size. In this study, we applied different analysis pipelines to a relatively large sample of individuals with depression to determine whether previous findings in depression can be replicated with these pipelines. We used a "standard" DTI algorithm and maps computed through a free-water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…Moreover, the only two DWI studies out of 16 that found no differences in the acute phase of the disorder between AN and controls, were not representative of the FA alteration assessment, because they used a different analysis approach, or because they focused on different variables (e.g., the interhemispheric connectivity instead of the FA), so they are not useful to reach a conclusion (Canna et al, ; Pfuhl et al, ). By the way, Bergamino, Kuplicki, Victor, Cha, and Paulus () showed that the differences between free water‐corrected and uncorrected FA in a large sample of depressed subjects are significant for the number of clusters found in the VBM analysis, but not when a TBSS pipeline was applied (they just found a reduction in significant volumes). PVE is a methodological problem for structural neuroimaging studies and numerous authors have investigated how the previous literature might therefore be biased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the only two DWI studies out of 16 that found no differences in the acute phase of the disorder between AN and controls, were not representative of the FA alteration assessment, because they used a different analysis approach, or because they focused on different variables (e.g., the interhemispheric connectivity instead of the FA), so they are not useful to reach a conclusion (Canna et al, ; Pfuhl et al, ). By the way, Bergamino, Kuplicki, Victor, Cha, and Paulus () showed that the differences between free water‐corrected and uncorrected FA in a large sample of depressed subjects are significant for the number of clusters found in the VBM analysis, but not when a TBSS pipeline was applied (they just found a reduction in significant volumes). PVE is a methodological problem for structural neuroimaging studies and numerous authors have investigated how the previous literature might therefore be biased.…”
Section: Discussionmentioning
confidence: 99%
“…were not representative of the FA alteration assessment, because they used a different analysis approach, or because they focused on different variables (e.g., the interhemispheric connectivity instead of the FA), so they are not useful to reach a conclusion Pfuhl et al, 2016). By the way, Bergamino, Kuplicki, Victor, Cha, and Paulus (2017) showed that the differences between free water-corrected and uncorrected FA in a large sample of depressed subjects are significant for the number of clusters found in the VBM analysis, but not when a TBSS pipeline was applied (they just found a reduction in significant volumes should preferably be used when analyzing this data, as it appears to be less susceptible to PVE and this could be the gold standard method to evaluate the putative role of specific brain area in AN, like the fornix (Kaufmann et al, 2017).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…It has been shown that elimination of extracellular free water contamination improves the sensitivity and specificity of most measures derived from conventional DTI (Albi et al, 2017;Salminen et al, 2016;Sepehrband et al, 2019). Although this correction techniques exist and have been used in pathological conditions (Bergamino, Kuplicki, Victor, Cha, & Paulus, 2017;Dumont et al, 2019;Ji et al, 2017;Ofori et al, 2017;Tanner et al, 2019) to date the majority of diffusion MRI studies do not consider free water effects on heathy aging brain (Albi et al, 2017;Chad, Pasternak, Salat, & Chen, 2018). Moreover, while FWE was initially developed to correct DTI derived metrics, it has recently been shown that the extracellular free water fraction may be a sensitive marker of age-related microstructural changes (Chad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches assume that the diffusion signal can be described by a single Gaussian process. However, at the imaging resolution typically achieved in a dMRI experiment – on the order of millimeters – this assumption is often violated …”
Section: Introductionmentioning
confidence: 99%
“…However, at the imaging resolution typically achieved in a dMRI experimenton the order of millimetersthis assumption is often violated. [3][4][5] The vast majority of studies on multiple diffusion components are based on multi-compartment models, which require prior knowledge of the number and structure of the compartments. Originally, Le Bihan et al 6 proposed a bi-exponential formulation of the isotropic diffusion signal defining the intra-voxel incoherent motion (IVIM) model, which quantifies the effect of blood pseudo-diffusion on the dMRI signal.…”
Section: Introductionmentioning
confidence: 99%